Diversity of parasitoid Hymenoptera in banana germplasm plantation Yogyakarta - Putra, Ichsan Luqmana Indra (Jurnal Biologi Udayana; Vol 23 No 1 (2019): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2019.v23.i01.p04, 2019)
Banana is one of the fruits in Indonesia. The development of its production in Indonesia has increased. However, there are several factors that can reduce the production, one of which is pests. Pests on bananas can be controlled with natural enemies, one of which is parasitoid. The study aimed to calculate the diversity and abundance of parasitoids in the Yogyakarta banana germplasm plantation. The research was carried out in an area of approximately 2 Ha from April to June 2018 with sampling taken once a week. Sampling method used was in the form of transect. The determination of the transect point is determined as far as 500m between sampling points. At each sampling point carried out 2 sampling methods. Direct method by taking pests on 3 banana plants at each point and indirect with insect net and yellow pan traps. The results found that Shannon-Wiener Index value was 3.29. 22 Hymenoptera parasitoid families were found with the highest morphospecies were superfamily Chalcidoidea and the highest number of individuals were Scelionidae.